Analisis Kebutuhan Sistem Informasi Akuntansi dalam Mendukung Implementasi PSAK 72 tentang Pendapatan dari Kontrak dengan Pelanggan : Studi Kasus pada PT GoTo Gojek Tokopedia Tbk - Merlindang Simamora; Bolivia Renata Sianipar (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
The implementation of PSAK 72 on Revenue from Contracts with Customers poses challenges for e-commerce firms with complex revenue streams. This study analyzes the functional requirements of Accounting Information Systems (AIS) to support PSAK 72 at PT GoTo Gojek Tokopedia Tbk. A qualitative case study approach was applied using secondary data from annual reports, prospectuses, and financial statement notes for 2019–2022. The results indicate three main AIS requirements: real-time integration with operational systems, a special module for transaction price allocation and variable considerations, and a flexible rule-based engine for revenue recognition. The challenges include massive transaction volumes, multi-service complexity, and dynamic business models. The study concludes that compliance with PSAK 72 requires transforming AIS from a conventional recording tool into an intelligent and integrated technological ecosystem.